(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
To evaluate serum anti-Mullerian hormone (AMH) in men with normal, reduced sperm concentration and in azoospermic men as a possible clinical marker of male factor infertility. Prospective study Private clinic of Dr. Yasir Al-Wattar and Al-Batool Teaching Hospital in Mosul. This study was conducted on one hundred male subjects aged less than 50 years for the period from July to November 2011, infertile men were classified according to their sperm count into oligospermics (n=28) and azoospermics(n=47), twenty five men were normal (n=25).Serum concentrations of FSH and Testosterone were measured using ELISA, serum Anti-Mullerian hormone concentrations were measured using AMH/MIS enzyme linked immunosorbant assay kit. Significant differences in serum AMH, FSH and Testosterone concentrations were found between normal, oligospermic & azoospermic men. AMH negatively correlated with FSH in oligospermic and azoospermic men and positively with testosterone in azoospermics and negatively with testosterone in oligospermics. Anti-Mullerian hormone should be evaluated in patients with oligospermia and azoospermia, it may serve as a marker of male infertility.